Pelatihan Pemanfaatan Media Sosial dalam Pemasaran Produk Pelaku UMKM Desa Ngasem - Doni Teguh Wibowo; Mas'ula Mas'ula (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2022)
The purpose of this service is to provide an understanding and implementation of the use of social media in the marketing of MSME products in Ngasem Village. To maximize these activities by making stickers and teaching how to properly package a product to creating social media accounts in the form of Instagram. This is aimed at marketing MSME products in Ngasem Village, Ngajum District, Malang Regency so that MSME products can be introduced to the wider community in order to get a wider market potential. Keywords: Marketing through social media, packaging, and SMEs Ngasem Ngajum